Вплив ендогенних факторів на процес управління фінансовими результатами комерційного банку - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Масюк, Юлія Володимирівна; Masiuk, Yuliia; Мачула, К.В.; Machula, K. (Мукачівський державний університет, 2024)
В статті визначено основні складові процесу управління фінансовими результатами комерційного банку. Також виявлено показники та перелік внутрішніх факторів, які впливають на формування фінансових результатів комерційних банків. Досліджено функції та сфери відповідальності наглядових органів управління комерційним банком відповідно до розроблених заходів фінансової стратегії функціонування банківського сектору в умовах воєнного стану. .Авторами виділено перспективи і труднощі розвитку банківської системи держави при умові забезпечення відповідними вимогами встановленими міжнародними нормативами, зокрема дотримання належного рівня ліквідності, формування обсягів активів, обсяги формування резервів та достатності капіталу, сум регулятивного капіталу банківських установ. Проведений аналіз впливу ендогенних факторів на процес управління фінансовими результатами комерційних банків дозволив виявити можливості підвищення їх прибутковості. In the modern market conditions of transformational transformations, the ability to effectively manage financial resources in such a way as to ensure profitability and increase the financial results of banking institutions has a significant impact on the financial stability and reliability of commercial banks. The main important conditions for the successful implementation of banking activities in the modern financial market remain endogenous factors, the emergence of which primarily includes changes in the main financial indicators: profitability of assets, profitability of capital, profitability of expenses, net spread, net interest margin, capital multiplier, coefficients of financial reliability and coverage. Effective management of the structural components of the financial result is carried out with the help of methods of financial profit management and financial planning, the use of which in banking practice can not only ensure the break-even activity of banking institutions, but also significantly increase their level of profitability. The article defines the main components of the process of managing the financial results of a commercial bank. Indicators and a list of internal factors that influence the formation of financial results of commercial banks have also been revealed. The functions and spheres of responsibility of the supervisory bodies of commercial bank management have been studied in accordance with the developed measures of the financial strategy of the functioning of the banking sector in the conditions of martial law. The authors highlighted the prospects and difficulties of the development of the banking system of the state under the condition of ensuring the corresponding requirements established by international standards, in particular, compliance with the appropriate level of liquidity, the formation of the volume of assets, the volume of the formation of reserves and capital adequacy, the amount of regulatory capital of banking institutions. The analysis of the influence of endogenous factors on the process of managing the financial results of commercial banks revealed the possibilities of increasing their profitability.
Influence of endogenous factors on the process of management of financial results of a commercial bank
Keywords: фінансовий результат; financial result; прибуток; profit; збиток; loss; управління фінансовим результатом; financial result management; комерційний банк; commercial bank